Economic Value of Water in the Rio Bravo Basin (Mexico) : The Case of Bajo San Juan, Juarez and Saltillo - Goicoechea, J. (World Bank, Washington, DC, 2013)
This paper evaluates the economic value of water in three locations in the Rio Bravo Basin. Formally known as the Bravo-Conchos, this basin overlaps across five Mexican states, beneath the Rio Bravo in northeastern Mexico. The paper also estimates the level of economic output in terms of value added for the main economic activities, using official statistics. The evaluation of water use provides elements of analysis needed to establish priorities in a quantitative fashion, utilizing an aggregation approach, while resorting to macroeconomic concepts. In terms of efficiency, there is a need to increase the municipal water tariffs to assist with the financial deficit faced by the water operators. Whether they are public agencies or private firms, the enterprises involved in all aspects of water services must be transparent and accountable in their actions and policy.